A structural and biochemical comparison of Ribonuclease E homologues from pathogenic bacteria highlights species-specific properties - Charlotte E. Mardle (Nature Portfolio, 2019)
Abstract Regulation of gene expression through processing and turnover of RNA is a key mechanism that allows bacteria to rapidly adapt to changing environmental conditions. Consequently, RNA degrading enzymes (ribonucleases; RNases) such as the endoribonuclease RNase E, frequently play critical roles in pathogenic bacterial virulence and are potential antibacterial targets. RNase E consists of a highly conserved catalytic domain and a variable non-catalytic domain that functions as the structural scaffold for the multienzyme degradosome complex. Despite conservation of the catalytic domain, a recent study identified differences in the response of RNase E homologues from different species to the same inhibitory compound(s). While RNase E from Escherichia coli has been well-characterised, far less is known about RNase E homologues from other bacterial species. In this study, we structurally and biochemically characterise the RNase E catalytic domains from four pathogenic bacteria: Yersinia pestis, Francisella tularensis, Burkholderia pseudomallei and Acinetobacter baumannii, with a view to exploiting RNase E as an antibacterial target. Bioinformatics, small-angle x-ray scattering and biochemical RNA cleavage assays reveal globally similar structural and catalytic properties. Surprisingly, subtle species-specific differences in both structure and substrate specificity were also identified that may be important for the development of effective antibacterial drugs targeting RNase E.